The Quality of Life of Adolescents with Type 1 Diabetes in Malang - Aloysia Ispriantari; Dian Pitaloka Priasmoro; Musthika Wida Mashitah (Journal of Ners and Midwifery, 2019)
Type 1 diabetes is a disease that can’t be cured but the quality of life of the patients can be maintained as much as possible. This study aimed to analyze the quality of life of adolescents with type 1 diabetes in Malang.  This study used cross sectional design. The sampling technique used total sampling by taking all adolescents (10-19 years) with type 1 diabetes who are still active in IKADAR Malang which were 24 adolescents. The quality of life of adolescents with type 1 diabetes was measured by the quality of life for youth questionnaire.  The result showed that the total score of the quality of life of adolescents with type 1 diabetes was 74.4±11.4 with the highest score was the impact on activities (92.3±12.4) and the lowest score was the parent issues (57.3±29.2). Higher score quality of life was in boys (75.5±12.9), age 10-14 years (75.3±11.7), disease duration  1-5 years (83.0±3.5) and last HbA1c was <7.5% (83.3±4.2). Healthcare providers especially nurse are expected to keep monitoring and improving the quality of life of adolescents with type 1 diabetes.